2016
DOI: 10.1513/annalsats.201506-390oc
|View full text |Cite
|
Sign up to set email alerts
|

Asthma Trigger Reports Are Associated with Low Quality of Life, Exacerbations, and Emergency Treatments

Abstract: Patients' perceptions of asthma triggers are important determinants of asthma outcomes, which can help identify individuals at risk for suboptimal asthma management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 34 publications
2
24
0
3
Order By: Relevance
“…We were able to confirm these findings in children and adolescents with asthma of varying severity in secondary or tertiary care. The impact of asthma triggers on HRQL may be explained by the fact that asthma triggers are associated with greater severity and frequency of asthma exacerbations, emergency treatments, healthcare visits and hospitalization . In addition, a higher number of asthma triggers may result in an increased perceived burden of asthma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We were able to confirm these findings in children and adolescents with asthma of varying severity in secondary or tertiary care. The impact of asthma triggers on HRQL may be explained by the fact that asthma triggers are associated with greater severity and frequency of asthma exacerbations, emergency treatments, healthcare visits and hospitalization . In addition, a higher number of asthma triggers may result in an increased perceived burden of asthma.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been shown that allergic disease‐specific HRQL in children was associated with grass pollen exposure and airway inflammation and generic HRQL in children was reduced during pollen season . In adults, previous research has suggested that mainly non‐allergic asthma triggers are associated with reduced asthma‐specific HRQL …”
Section: Introductionmentioning
confidence: 99%
“…As the information conditions in our experiment mimic aspects of trigger-related information or advice that is given to patients by physicians or in internet-based asthma information, our findings may be of relevance to the management of asthma in daily life, as they suggest that experience-based beliefs about asthma triggers are shaped by prior information about asthma causality, as well as individual differences in symptom perception. The effects of prior information on generalization of trigger beliefs may be especially relevant, as they may help to explain the individual differences in asthma trigger beliefs that have been observed in individuals with asthma (Ritz et al, 2016) and associated differences in trigger avoidance strategies (Vernon et al, 2012). …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in day-to-day asthma management, individuals with asthma often report being uncertain about their personal triggers and trigger avoidance strategies (Caress et al, 2002; Trollvik and Severinsson, 2004). In addition, individuals show a marked variation in the type and number of asthma triggers they identify, with a higher number of self-identified asthma triggers being associated with worse asthma outcomes, even when controlling for other measures of asthma severity (Ritz et al, 2006, 2016; Janssens and Harver, 2015). Taken together, these findings suggest difficulties and inaccuracies in the process of asthma trigger identification or the detection of trigger-symptom contingencies.…”
Section: Introductionmentioning
confidence: 99%
“…In some studies, stress has been an even stronger risk factor than environmental exposures for asthma morbidity [65]. Multiple sources of stress, commonplace in the disadvantaged asthma patient, have been associated with increased asthma morbidity.…”
Section: Psychosocial Stress: Increased In the Disadvantaged Patientmentioning
confidence: 99%